Uit de donkere dagen van voor linguistic turn oftewel wat J. M. Coetzee in de bekentenis van Willem Termeer zag en wat hij daarmee deed - Jerzy Koch; Pawel Zajas (Tydskrif vir Letterkunde, 2009)
The South African Nobel Prize winner, J. M. Coetzee has a particular connection to the Netherlands. For instance, he had reviewed Dutch literature for the New York Times (the reviews were later included in a book called Stranger Shores: essays 1986–1999) and he translated and compiled an anthology of Dutch poetry (Landscape with Rowers, 2004) for the English readership. Moreover, his books are frequently published in their Dutch translation prior to their official English releases. In 1976, Coetzee translated a novel by Marcelus Emants Een nagelaten bekentenis (1894), published in English as A Posthumous Confession. Parallel to this translation work, Coetzee also worked on his second novel In the Heart of the Country (1977). This paper is devoted to a detective-like tracing of reflections that Coetzee’s close reading of the Dutch novelist might have left in his own book. Why did Coetzee in the first place decide to translate Emants’ novel? What was its appeal that attracted him so much? What was Coetzee’s reading of Emants back in the 1970s?